2022
DOI: 10.1007/s12035-022-02758-x
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death-1 Deficiency Aggravates Motor Dysfunction in MPTP Model of Parkinson's Disease by Inducing Microglial Activation and Neuroinflammation in Mice

Abstract: Abundant reactive gliosis and neuroin ammation are typical pathogenetic hallmarks of brains inParkinson's disease (PD) patients, but regulation mechanisms are poorly understood. We are interested in role of programmed death-1 (PD-1) in glial reaction, neuroin ammation and neuronal injury in PD pathogenesis. Using PD mouse model and PD-1 knockout (KO) mice, we designed wild-type-control (WT-CON), WT-1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (WT-MPTP), PD-1-KO-control (KO-CON) and PD-1-KO-MPTP (KO-MPTP), and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Moreover, GFAP and Iba‐1 expression in the SN was also enhanced by MPTP treatment, suggesting the activation of microglia and astrocytes as well as the trigger of neuroinflammation in MPTP‐induced PD mouse models, which was consistent with the previous studies. [ 45,46 ] Vincamine was previously demonstrated to exert potent suppression of inflammation in lipopolysaccharide‐induced mouse models of acute lung injury by increasing anti‐inflammatory cytokine expression but reducing pro‐inflammatory cytokine expression. [ 47 ] Vincamine administration can also reduce serum levels of TNF‐α, IL‐1β, and IL‐6 in experimental rat models of renal ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, GFAP and Iba‐1 expression in the SN was also enhanced by MPTP treatment, suggesting the activation of microglia and astrocytes as well as the trigger of neuroinflammation in MPTP‐induced PD mouse models, which was consistent with the previous studies. [ 45,46 ] Vincamine was previously demonstrated to exert potent suppression of inflammation in lipopolysaccharide‐induced mouse models of acute lung injury by increasing anti‐inflammatory cytokine expression but reducing pro‐inflammatory cytokine expression. [ 47 ] Vincamine administration can also reduce serum levels of TNF‐α, IL‐1β, and IL‐6 in experimental rat models of renal ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al. ( 344 ) reported that loss of programmed death-1 (PD-1) exacerbates motor impairment in the MPTP model of PD by triggering microglial activation and neuroinflammation in mice. Utilizing a PD mouse model and PD-1 KO mice, these authors established distinct experimental groups: WT-CON, WT-MPTP, KO-CON, and KO-MPTP, which stand for wild-type-control, wild-type-1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, PD-1-KO-control, and PD-1-KO-MPTP, respectively.…”
Section: Navigating the Course Of Neuroinflammation And Microglial Ac...mentioning
confidence: 99%
“…Cheng et al (344) reported that loss of programmed death-1 (PD-1) exacerbates motor impairment in the MPTP model of PD by triggering microglial activation and neuroinflammation in mice. Utilizing a PD mouse model and PD-1 KO mice, these authors established distinct experimental groups: WT-CON, WT-MPTP, KO-CON, and KO-MPTP, which stand for wild-type-control, wildtype-1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine, PD-1-KOcontrol, and PD-1-KO-MPTP, respectively.…”
Section: Quality Assessmentmentioning
confidence: 99%